Peningkatan Akurasi Kontrol Arah Kapal Menggunakan Sensor Kompas BNO055 - Setiyono, Dwi Agus; Afif Zuhri Arfianto; Dimas Pristovani Riananda; Agus Khumaidi; Noorman Rinanto; Zindhu Maulana Ahmad (Indonesian Society of Applied Science (ISAS), 2025)
The accuracy of a ship's heading measurement is an important element in ensuring the ship moves towards its destination precisely and safely. One of the key parameters in this system is the ship's heading, which indicates the direction of the ship relative to a specific reference point, such as magnetic north. However, heading measurements are often affected by environmental disturbances, magnetic interference and sensor calibration errors, which can degrade measurement accuracy. This research proposes the use of the BNO055 sensor, which combines an accelerometer, gyroscope and magnetometer in a single module to measure ship orientation in three dimensions. An STM32 microcontroller is used to process the data from the BNO055 sensor and calculate the ship's heading and relative bearing with high precision. The calculation results are then displayed on the Nextion Display, providing visual information needed by the user. Test results show that the system provides high accuracy, with an average percentage error of 0.002% for heading and 0.208% for angle. The system can steer the ship with high precision, despite magnetic field disturbances. Thus, this BNO055 and STM32-based system is expected to improve efficiency and accuracy in ship direction measurement applications.